2011
DOI: 10.3233/bmr-2011-0293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients' response to pulsed radiofrequency treatment applied to the suprascapular nerve in patients with chronic shoulder pain

Abstract: Pulsed radiofrequency technique application to the suprascapular nerve for 480 seconds shows remarkable improvement at patients' chronic shoulder pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…RF treatment of SSN may be an alternative method of providing prolonged relief for chronic shoulder pain12). Conventional RF treatment destroys nerve tissue, thus preventing the propagation of pain signals and providing sustained pain relief19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RF treatment of SSN may be an alternative method of providing prolonged relief for chronic shoulder pain12). Conventional RF treatment destroys nerve tissue, thus preventing the propagation of pain signals and providing sustained pain relief19).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the effect of PFR neuromodulation for shoulder pain12). Shah and Racz20) described the case of a patient with severe post-traumatic pain who received repeated PRF neuromodulation on the suprascapular nerve.…”
Section: Discussionmentioning
confidence: 99%
“…As Rohof et al . first defined PRF applied to the SNN, PRF have been widely used to shoulder pain in clinical trials, which demonstrated that PRF could achieve desirable results of relatively long‐term pain relief and function restoration without risking paralysis of the supraspinatus and infraspinatus muscles . However, the majority of these treatments were prospective studies without control groups, retrospective studies, or case series with low level of evidence so that evidence‐based trials are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In a report of three cases who received therapy to the glenohumeral joint, Ozyuvaci et al reported PRF therapy as a recommendable treatment modality [22]. In addition, PRF studies in the management of chronic shoulder pain often evaluated the application to the suprascapular nerve rather than application into and around the joints [14,23]. In a series of 40 patients who received PRF therapy to the suprascapular nerve due to impingement syndrome, the patients were evaluated using the Likert scale and Oxford Shoulder Score for six months, and it was found to be an effective treatment modality and the effects of this therapy were sustained in the long term [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 40 patients who received PRF therapy to the suprascapular nerve due to impingement syndrome, the patients were evaluated using the Likert scale and Oxford Shoulder Score for six months, and it was found to be an effective treatment modality and the effects of this therapy were sustained in the long term [14]. In another study including 57 patients with chronic shoulder pain resistant to medical treatment, PRF was applied to the suprascapular nerve for 480 seconds, indicating a statistically significant recovery during follow-up [23]. Moreover, in a randomized controlled trial carried out by Gofeld et al in 22 patients with chronic shoulder pain, the first group received lidocaine and the second group received lidocaine + PRF therapy to the suprascapular nerve during a six-month follow-up [24].…”
Section: Discussionmentioning
confidence: 99%